Genetic Approaches for Controlling CRISPR-based Autonomous Homing Gene Drives - Chennuri, Pratima R.; Adelman, Zach N.; Myles, Kevin M. (Frontiers in Bioengineering and Biotechnology, 2022)
CRISPR-based autonomous homing gene drives are a potentially transformative technology with the power to reduce the prevalence of, or even eliminate vector-borne diseases, agricultural pests, and invasive species. However, there are a number of regulatory, ethical, environmental, and sociopolitical concerns surrounding the potential use of gene drives, particularly regarding the possibility for any unintended outcomes that might result from such a powerful technology. Therefore, there is an imminent need for countermeasures or technologies capable of exerting precise spatiotemporal control of gene drives, if their transformative potential is ever to be fully realized. This review summarizes the current state of the art in the development of technologies to prevent the uncontrolled spread of CRISPR-based autonomous homing gene drives.